ANALISIS PERAN PERSON JOB-FIT TERHADAP HUMAN RESOURCES DEVELOPMENT PRACTICES DALAM MENINGKATKAN EMPLOYEE JOB PERFORMANCE - Simon Petrus Wenehenubun (Jurnal Humanipreneur, 2023)
This study aims to analyze the moderating role of person-job fit in HRD Practices and employee work performance. We used a qualitative method with in-depth interviews with ten managers from 4 coal mining service companies in Indonesia. Respondents have more than five years of work experience in the field of Human Resource Development and Training. The findings show that HRDP improves employee performance. The moderating role of personal-job fit will strengthen HRDP in improving employee performance.